Effects of Different Temperatures on the Development and Reproduction of Sitobion miscanthi From Six Different Regions in China - Sun, Jingxuan; Tan, Xiaoling; Li, Qian; Francis, Frédéric; Chen, Julian (Frontiers in Ecology and Evolution, 2022)
The increase in temperature caused by global warming has greatly impacted plant growth and pest population dynamics worldwide, especially for wheat aphids. In this study, Sitobion miscanthi individuals from six geographic populations located in different wheat-producing areas in China were compared with regard to their growth, development, survival, and reproductive under different temperature conditions (17, 22 and 27°C). A population life-table analysis and a correlation analysis between geographic factors and S. miscanthi longevity or fecundity were also performed. Temperature significantly affected the nymphal development duration (NDD), the adult longevity (ALY) and the fecundity (AFY) of the aphids, however, latitude can only affect the NDD and ALY. There is an obvious interaction between temperature and latitude on the NDD, ALY and AFY. The NDD in the three northern populations was significantly shorter than that in the southern populations. The ALY in northern populations was significantly longer than that in southern populations at different temperatures. Except for Yinchuan population was no significantly different under different degrees, the ALY of other populations was significantly shortened at 27 °C. The AFY of northern populations was significantly lower than that of southern populations at 22°C, while significantly higher at 27°C. With the increase of temperature, the fecundity of northern population gradually decreased from 17℃ to 22℃, while the southern population suddenly decreased at 27℃. The curves of survival rate (sxj) in southern populations were significantly shorter than that of northern population. In addition, there was a positive correlation between latitude and longevity under the three degrees, however, only at 27℃, there was a positive correlation between latitude and fecundity. Our result proved that the higher reproductive rate of southern population requires aphids to live at the suitable ambient temperature, and aphid populations in the north have a wider ecological amplitude. The results will be helpful for predicting the potential aphid outbreaks in China's main wheat areas under suitable conditions.